The Influence Of Entrepreneurship Education, Entrepreneurial Mindset and Peer Groups On Entrepreneurial Readiness Of SMK Students Through Mediation Of Entrepreneurial Self-Efficacy - Siti Neno Muawiyah; Prof. Dr. Dedi Purwana, E.S., M.Bus; Dr. Agus Wibowo, S.Pd.i, S.Pd., M.Pd (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyse the effect of entrepreneurship education, entrepreneurial mindset, and peer group on entrepreneurial readiness of vocational students with mediation of entrepreneurial self-efficacy. Primary data in this study were obtained through non-probability sampling technique with purposive sampling method, where respondents were selected based on certain criteria. The research sample consisted of 280 students of class XII of state vocational schools in Bekasi Regency who had received entrepreneurship education. Data collection was conducted through an independent survey using an online questionnaire. The research method used is descriptive quantitative with Structural Equation Modelling-Partial Least Square (SEM) approach. The results showed that entrepreneurship education, entrepreneurial mindset, and peer group have a positive and significant effect on entrepreneurial readiness of vocational students. In addition, entrepreneurial self-efficacy was shown to act as a mediating variable in the relationship between the independent variables and entrepreneurial readiness. The findings emphasise the importance of entrepreneurship education as well as psychological and social factors in enhancing vocational students' entrepreneurial readiness.